A Qualitative Analysis of the Experiences of Drug Rehabilitation Clients in Facing Social Stigma - Dery Zelviro Ronanda; Miftahuddin Miftahuddin; M. Fahli Zatrahadi; Silawati Silawati (SCHOULID: Indonesian Journal of School Counseling, 2026)
This study aims to explore and understand the experiences of drug rehabilitation clients in confronting social stigma in the city of Pekanbaru, Indonesia. Using a qualitative approach with a phenomenological design, the research involved 10 participants selected through purposive sampling. Data were collected via semi-structured in-depth interviews and analyzed thematically. Results identified five major themes: (1) external stigma manifested as labeling, discrimination, and social rejection; (2) self-stigma as the internalization of negative societal views; (3) active coping strategies including self-proving, spirituality, and cognitive reframing; (4) the dual impact of stigma on the recovery process; and (5) the protective role of social support. These findings affirm that the success of drug rehabilitation is not solely determined by clinical intervention, but also by the conditions of social acceptance and environmental support surrounding the individual.